The Impact of Credit Risk in the Financial Performance of Private Commercial Banks in Syria (Journal of Hama University, 2020)
The study aimed to identify the impact of credit risk on the financial performance of private commercial banks in Syria. To achieve this goal, annual data were collected for a sample of eleven private commercial banks during the period between 2008 and 2018. The study data was mainly collected from the financial reports of the studied banks.The independent variable represented by credit risk was measured using the proportion of doubtful loan allocations and the ratio of non-performing loans, while the dependent variable of financial performance was measured using the rate of return on equity, the rate of return on assets and the percentage of financial leverage. For the purpose of analyzing the study data, data panel models were used to test the relationship between independent and dependent variables, and a statistical program (Eviews 10) was used in the data analysis process. The results of the study showed a positive effect for both the ratio of (doubtful loan allocations, non-performing loans) in the rate of return on equity, and the presence of a positive effect for both the proportion of (doubtful loan allocations, non-performing loans) in the rate of return on assets. The results of the study also showed a positive effect for both the ratio of (doubtful loan allocations, non-performing loans) in the financial leverage ratio, which indicates that credit risk management has a role in improving the financial performance of private commercial banks in Syria.